Aktivitas Antioksidan Ekstrak Metanol Daun Tandui (Mangifera rufocostata K.)Menggunakan Metode DPPH - Eka Fitri Susiani; Revita Saputri; Helmina Wati; Fitria Mahmudah; Vebruati Vebruati (Universitas Borneo Lestari, 2024)
Free radicals are highly reactive compounds because they have unpaired electrons so that they can interact with body cell molecules, this can cause various diseases. Antioxidants are compounds that can ward off free radicals. Plants of the genus Mangifera are known to have antioxidant activity, one of which is Mangifera rufocostata Kosterm, a typical plant of South Kalimantan known as tandui. The purpose of this study was to determine the antioxidant activity of the methanol extract of the leaves of tandui (Mangifera rufocostata Kosterm.) using the DPPH test method. Phytochemical screening and antioxidant activity tests were performed using a UV-Vis spectrophotometer. The compounds contained in the methanol extract of tandui leaves (Mangifera rufocostata Kosterm.) are phenols, flavonoids, and tannins. The IC50 value of quercetin obtained was 2.39 ppm and the IC50 value of the tandui leaf methanol extract (Mangifera rufocostata Kosterm.) which was obtained was 8.222 ppm. Tandui leaf methanol extract has very strong antioxidant activity.